Design And Construction Of RH2000 Cybernatics Hand - Ali @ Ibrahim, Fariz; Jamaluddin, Muhammad Herman; Abas, Norafizah; Miskon, Muhammad Fahmi; Shukor, Ahmad Zaki; Norizan, Muhammad Alif; Juhari, Mohamad Fakri (Penerbit UTM Press, 2015)
-